Bioactive Secondary Metabolites from the Mangrove Endophytic Fungi Nigrospora oryzae - Antonius Rolling Basa Ola; Titus Lapailaka; Hermania Em Wogo; Julinda Bendalina Dengga Henuk; Agnes Simamora; Lince Mukkun; Peter Proksch; Chong Dat Pham (Indonesian Journal of Chemistry, 2021)
Mangrove forest has a distinctive habitat adapting with marine and terrestrial environment. Chemical investigation of the extract from mangrove endophytic fungi Nigrospora oryzae had resulted in the isolation of sterigmatocystin (1) and pestalopyrone (2). The structure of sterigmatocystin (1) and pestalopyrone (2) were elucidated using mass, UV and NMR spectrometers together with the comparison with the literature data. The study also showed that sterigmatocystin displayed moderate cytotoxicity but it could be further developed as antiviral and antibacterial agent based on the SAR information reported from its analogue and derivatives.